Selective Pressure of Temperature on Competition and Cross-Feeding within Denitrifying and Fermentative Microbial Communities - Hanke, Anna; Berg, Jasmine; Hargesheimer, Theresa; Tegetmeyer, Halina E.; Sharp, Christine E.; Strous, Marc (Frontiers in Microbiology, 2016)
In coastal marine sediments, denitrification and fermentation are important processes in the anaerobic decomposition of organic matter. Microbial communities performing these two processes were enriched from tidal marine sediments in replicated, long term chemostat incubations at 10ºC and 25ºC. Whereas denitrification rates at 25ºC were more or less stable over time, at 10ºC denitrification activity was unstable and could only be sustained either by repeatedly increasing the amount of carbon substrates provided or by repeatedly decreasing the dilution rate. Metagenomic and transcriptomic sequencing was performed at different time points and provisional whole genome sequences and gene activities of abundant populations were compared across incubations. These analyses suggested that a temperature of 10ºC selected for populations related to Vibrionales/Photobacterium that contributed to both fermentation (via pyruvate/formate lyase) and nitrous oxide reduction. At 25ºC, denitrifying populations affiliated with Rhodobacteracaea were more abundant. The latter performed complete denitrification, and may have used carbon substrates produced by fermentative populations (cross-feeding). Overall, our results suggest that a mixture of competition – for substrates between fermentative and denitrifying populations, and for electrons between both pathways active within a single population –, and cross feeding – between fermentative and denitrifying populations – controlled the overall rate of denitrification. Temperature was shown to have a strong selective effect, not only on the populations performing either process, but also on the nature of their ecological interactions. Future research will show whether these results can be extrapolated to the natural environment.